The Program Assessment Guide: An Approach for Structuring Contextual Knowledge and Experience to Improve the Design, Delivery, and Effectiveness of Nutrition Interventions - Pelletier, David; Corsi, Allison; Hoey, Lesli; Faillace, Silvana; Houston, Robin (The Journal of nutrition, 2011)
As evidence from small-scale trials has accumulated concerning the efficacy of low-cost interventions to address undernutrition, the design, implementation, and strengthening of large-scale programs to deliver these interventions has become a high priority. This scaling up process involves a large number of technical, logistical, administrative, political, and social considerations and little research exists on how to address these in a systematic way. This paper introduces the Program Assessment Guide (PAG), a set of analysis and decision tools that seeks to fill this gap, and reports on its application in Kyrgyzstan and Bolivia. The PAG places a special focus on eliciting and systematizing contextual knowledge and experience through a structured, participatory workshop and is grounded in theory, principles, and experience from program planning, management, change management, and intervention planning. When applied in Kyrgyzstan and Bolivia, the PAG was successful in helping workshop participants identify key implementation bottlenecks, questionable assumptions in the program theory, and feasible ways to address some of the shortcomings. These experiences also identified the need for a number of modifications to the PAG related to the workshop design itself, the preparations prior to the workshop, and follow-up after the workshop. The PAG represents one approach for strengthening decisions related to the design and large-scale implementation of interventions. The development and full-scale testing of alternative methods such as these for strengthening program analysis and decision making is an important and intellectually challenging subject for further research.